Factors Affecting Customer Satisfaction of E- Payments System - Shrestha, Ranu (KMC Research Journal, 2020)
The main objective of the study was to identify the factors that affect consumer satisfaction towards e payment. Price, quality, information, and security are taken to measure the customer satisfaction towards e-payment. Survey questionnaire were used to collect the primary data. Convenient sampling was used for the sampling. Altogether, 150 samples were considered for the collection of the necessary data. Descriptive as well as inferential statistical tools were used to analyze the primary data. Mean and standard deviation were used as a descriptive statistic to describe the situation of collected data and correlation was used as inferential statistics has used to examine the relationship of independent variables with customer satisfaction.From the result of correlation analysis, it is found that there is a significant positive high correlation of security and information with customer satisfaction. Moreover, it is found that there is moderate correlation between quality and customer satisfaction. Lastly, there is low correlation between price and customer satisfaction towards e-payments.